A phantom assessment of achievable contouring concordance across multiple treatment planning systems. Issue 3 (December 2015) - Pogson, Elise M.; Begg, Jarrad; Jameson, Michael G.; Dempsey, Claire; Latty, Drew; Batumalai, Vikneswary; Lim, Andrew; Kandasamy, Kankean; Metcalfe, Peter E.; Holloway, Lois C.
Abstract: In this paper, the highest level of inter- and intra-observer conformity achievable with different treatment planning systems (TPSs), contouring tools, shapes, and sites have been established for metrics including the Dice similarity coefficient (DICE) and Hausdorff Distance. High conformity values, e.g. DICEBreast_Shape = 0.99 ± 0.01, were achieved. Decreasing image resolution decreased contouring conformity.